2021
DOI: 10.3390/nu14010152
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Omega-3 Polyunsaturated Fatty Acids in Pediatric Food Allergy

Abstract: Polyunsaturated fatty acids (PUFAs) are involved both in immune system regulation and inflammation. In particular, within the PUFAs category, omega-3 (ω-3) may reduce inflammation, whereas omega-6 (ω-6) PUFAs are generally considered to have a proinflammatory effect. Recent evidence highlights an imbalance in the ω-3: ω-6 ratio with an increased intake of ω-6, as a consequence of the shift towards a westernized diet. In critical age groups such as infants, toddlers and young children, as well as pregnant and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…While individuals who consume higher proportions of red meat and fats have a higher risk of IBD, others who predominantly consume fibers from vegetables and fruits have a lower risk [ 101 , 102 ]. Regarding dietary fat content, particularly polyunsaturated fatty acids, recent data indicate that a high omega-6 to omega-3 ratio, typical of Western-style diets, is associated with proinflammatory effects [ 103 ]. Furthermore, polyunsaturated fatty acids have been shown to exert not only effects on the immune response, directly acting on immune cells, but also influence the composition of the gut microbiota, thereby affecting host–microbiome interactions at different levels [ 104 ].…”
Section: Influence Of the Exposomementioning
confidence: 99%
“…While individuals who consume higher proportions of red meat and fats have a higher risk of IBD, others who predominantly consume fibers from vegetables and fruits have a lower risk [ 101 , 102 ]. Regarding dietary fat content, particularly polyunsaturated fatty acids, recent data indicate that a high omega-6 to omega-3 ratio, typical of Western-style diets, is associated with proinflammatory effects [ 103 ]. Furthermore, polyunsaturated fatty acids have been shown to exert not only effects on the immune response, directly acting on immune cells, but also influence the composition of the gut microbiota, thereby affecting host–microbiome interactions at different levels [ 104 ].…”
Section: Influence Of the Exposomementioning
confidence: 99%
“…In the papers included herein, higher maternal and newborn proportions of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) were related to a decreased prevalence of IgE-associated illness (p = 0.01-0.05) in a dose-dependent manner [19]. According to the findings of a systematic review conducted by Sartorio (2021), supplementation with PUFAs inhibits allergic response in preclinical studies [27]. Still, other studies investigating general atopy indicated that long chain PUFA supplementation during pregnancy did not decrease the general rate of IgE-associated allergies in the first year of life; however, atopic eczema and egg sensitization were reduced [14,17].…”
Section: Discussionmentioning
confidence: 99%
“…Data on consumption of LCn3s in the antenatal period and early infancy have been reproduced in many studies worldwide for prevention of inhalant allergies, as summarized in recent reviews [ 141 , 142 ]. The data on food allergy are not as reproducible or as strong.…”
Section: The Bigger Picture Of Preventionmentioning
confidence: 99%